PENYULUHAN HUKUM TENTANG GERAKAN NASIONAL ANTI NARKOBA DAN BAHAYA SOSIAL DI KANTOR MAJELIS ULAMA JAKARTA UTARA “Problematika Narkoba dan Solusi Terpadu dari Perspektif Hukum” - Azis, Rizka Amelia; Afif, Ahmad Sururi; Susetio, Wasis; Olivia, Fitria; Judge, Zulfikar; Nurhayani, Nurhayani; Hikmawati, Elok; Saragih, Horadin; Arianto, Henry; Hartadi, I Gede (Jurnal Pengabdian Masyarakat AbdiMas, 2025)
AbstractThe abuse of narcotics in Indonesia has shown a significant increase, accompanied by broad social impacts, particularly on young people and vulnerable groups. This Community Service Program (PkM) was conducted by lecturers of the Faculty of Law at Universitas Esa Unggul in collaboration with the Indonesian Ulema Council (MUI) of North Jakarta through the National Anti-Narcotics Movement on 26 October 2025. The program aimed to provide legal education, enhance understanding of the social consequences of narcotics, and promote integrated prevention strategies grounded in legal norms and religious values. The methods employed included legal counseling, lectures, interactive discussions, and case analysis based on Law No. 35 of 2009 on Narcotics, Law No. 5 of 1997 on Psychotropics, and the National Criminal Code (Law No. 1 of 2023). The findings show that narcotics abuse is not solely a criminal matter but also a complex issue involving health, social conditions, morality, and institutional governance. This activity strengthened collaboration between universities, communities, and religious institutions in building an effective prevention ecosystem. Ultimately, accurate legal education has proven to improve public literacy on rehabilitation, criminal liability, and the role of families in preventing narcotics abuse. Keywords: narcotics, criminal law, rehabilitation, prevention, social harm. AbstrakPenyalahgunaan narkoba di Indonesia menunjukkan peningkatan signifikan dengan dampak sosial yang meluas, khususnya pada generasi muda dan kelompok rentan. Kegiatan Pengabdian kepada Masyarakat (PkM) ini dilakukan oleh Dosen Fakultas Hukum Universitas Esa Unggul bekerja sama dengan Majelis Ulama Indonesia (MUI) Jakarta Utara melalui program Gerakan Nasional Anti Narkoba pada 26 Oktober 2025. Tujuan kegiatan adalah memberikan edukasi hukum, pemahaman dampak sosial narkoba, serta strategi pencegahan terpadu berbasis hukum dan nilai keagamaan. Metode yang digunakan meliputi penyuluhan hukum, ceramah, diskusi interaktif, serta analisis kasus berdasarkan UU No. 35 Tahun 2009 tentang Narkotika, UU No. 5 Tahun 1997 tentang Psikotropika, serta KUHP Nasional (UU No. 1 Tahun 2023). Hasil kegiatan menunjukkan bahwa penyalahgunaan narkoba tidak hanya persoalan kriminal, tetapi juga persoalan kesehatan, sosial, moral, dan kelembagaan. Kegiatan ini memperkuat kolaborasi kampus–masyarakat–institusi keagamaan dalam membangun ekosistem pencegahan yang efektif. Pada akhirnya, edukasi hukum yang tepat terbukti meningkatkan literasi masyarakat mengenai rehabilitasi, pertanggungjawaban pidana, serta peran keluarga dalam pencegahan narkoba. Kata kunci: narkotika, hukum pidana, rehabilitasi, pencegahan, bahaya sosial.